The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00167-011-1576-z
|View full text |Cite
|
Sign up to set email alerts
|

The arrangement and the attachment areas of three ACL bundles

Abstract: This study clarified the arrangement of three fiber bundles of ACL and detailed geographical locations of their attachment sites. The detailed anatomic description of the natural ACL attachment might suggest to surgeons where to make tunnels during anatomical double/triple bundle ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 46 publications
(141 reference statements)
4
50
0
Order By: Relevance
“…In 22 knees with the exception of the 2 knees depicted in two fiber bundles, the fiber arrangement of each bundle (Fig. 4) was same with that of the previous cadaveric report (Otsubo et al, 2012; Fig. 1).…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…In 22 knees with the exception of the 2 knees depicted in two fiber bundles, the fiber arrangement of each bundle (Fig. 4) was same with that of the previous cadaveric report (Otsubo et al, 2012; Fig. 1).…”
Section: Resultssupporting
confidence: 78%
“…MacKay et al (2014) first reported the triple-bundle depiction, but the triple bundles were identifiable in only 15 out of 73 knees (20.5%) on MRI. However, in the previous studies using the fresh-frozen cadaveric knees, the triple-bundle ACL was macroscopically identifiable in all cases (Fujie et al, 2011;Kato et al, 2012;Otsubo et al, 2012;Suzuki et al, 2015).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations